Sensory Attributes of Composite Breads from Shelf Storable Orange-Fleshed Sweetpotato Puree - Muzhingi, Tawanda; Owade, Joshua Ombaka; Abong, George Ooko; Okoth, Michael Wandayi; Heck, Simon; Low, Jan; Mbogo, Daniel; Malavi, Derrick (Walter de Gruyter GmbH, 2018)
Technological advances in baking have enabled the use of bread as a food vehicle for various nutrients through use of composite flours. Orange-fleshed sweetpotato (OFSP) puree subjected to cold chain storage has been used to enrich bread with beta-carotene. However, this has proven expensive and inconsistent in supply of puree. This study sought to develop shelf-storable OFSP puree bread with similar sensory qualities to fresh OFSP puree bread. Bread in which two treatments of shelf-storable OFSP puree (treatments 1 and 2 with 0.5% potassium sorbate+0.5% sodium benzoate+1% citric acid and 0.2% potassium sorbate+0.2% sodium benzoate+1%citric acid respectively) were incorporated at 30% and 40% and were subjected to descriptive sensory analysis with white and fresh puree breads as controls. The results indicate that both the 40% and 30% wheat substitution with either treatment 1 or 2 OFSP puree bread are acceptable to the consumers, p<0.05. The saltiness, smoothness and crumb color scores for shelfstorable OFSP puree bread were similar to those of fresh puree bread but were significantly (p<0.05) higher than that of white bread. Shelf-storable OFSP puree bread had similar sensory profile to fresh OFSP puree bread thus can be exploited as an alternative to fresh puree bread.